INTERAKSI HUKUM POSITIF DAN BUDAYA DALAM PERTUNJUKAN MUSIK DITINJAU DARI HUKUM HAK CIPTA - Adil, Hendy Rizki Posma; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
Discussion about copyright is an exclusive right given to those who are creative on the basis of a creation that has been successfully created and can be enjoyed by the general public in the realm of scientific knowledge, works of art and literature. Normatively, the formal rules regarding copyright in Indonesian law are regulated through Law No. 28 of 2914. The concept of protection from copyright law itself in this case includes of protection from copyright law itself in this case includes moral rights and economic rights. Meanwhile, the meaning of moral rights is a type of right that protects the moral value of the creator, this is to keep his name attached to a work that has been created, while economic rights regulate the economic value generated by a creative work for each creator to be able to enjoy it for the benefit of the work. which produces commercial value. Music or songs are form of creation in the field of art which is the object of copyright protection. Nowadays, there are many musical performances, where singers usually perform songs belonging to or created by other people. As for the activity of performing other people’s songs and music, sometimes there is a profit value, of course in the work. Even though in society’s culture, especially musical artists, performing other people’s works is common occurrence, if the singer performing someone else’s song makes a profit, then it is only natural that the original creator gets royalties.Keywords: Copyright, Music Performance, Legal Culture